TRANSFORMASI SPIRITUALITAS: DISKURSUS TEOLOGI TENTANG KONSEP MANUSIA BARU DALAM KOLOSE 3:5-17 - Yunus Monei; Roberth Ruland Marini; Pestaria Happy Kristiana (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2024)
The research addressed the gap between the theological concept of the new man in Christ and its implementation in everyday Christian life, highlighting the need for a deeper understanding of this concept to address uncertainties and misconceptions among believers. Through a qualitative theological approach, the study explored the subjective meaning of religious beliefs, religious practices, and biblical texts. Findings indicated that the concept of the new man emphasized the importance of spiritual transformation and the embodiment of values of love and truth in Christian life practices. Implications included shifts in self-perception and perceptions of others, conflict resolution, and understanding of true life purposes. The novelty of thought lay in the comprehensive application of the concept of the new man in the text of Colossians 3:5-17, aiming to bring positive impacts to individuals and communities. Thus, understanding and embodying this concept called believers to live in freedom, sanctity, and authentic love.